INNOVATION MANAGEMENT CAPACITY IN DIGITAL TRANSFORMATION OF LOCAL GOVERNMENT: A QUALITATIVE CASE STUDY OF PUBLIC SERVICES IN MAKASSAR, INDONESIA - Ali Anas; Uddin Sore; Wina Ayu Giswanti; Syamsuddin Maldun; Andi Tenri Habibah (Journal of Governance and Law Reform, 2026)
Digital transformation of local governments is often introduced through the development of electronic platforms. Still, its success is largely determined by the ability of public organizations to manage innovation, create effective work processes, and prioritize citizen-centered services. This study aims to analyze the innovation management capacity of local governments in the digital transformation of public services in Makassar City, Indonesia. The study used a qualitative approach with an exploratory case study design. Data were collected through semi-structured interviews, observations of service practices, and analysis of relevant documents, including digital service procedures, internal reports, policy documents, and contextual digital-government data. Analysis was conducted thematically through iterative coding, data reduction, category development, and triangulation between sources. The results show that digital service platforms and formal policy commitments are in place. However, service implementation still operates in a hybrid manner, ranging from online registration with manual verification, physical filing, and parallel data input. Apparatus adaptation is driven more by informal learning, peer mentoring, problem-solving through instant messaging applications, and leadership monitoring, rather than by systematic training. Leadership supports digital adoption through daily oversight, coordination with technical units, and operational problem-solving, but hierarchical decision-making and application fragmentation limit end-to-end service integration. For citizens, digital transformation improves initial access, queue management, and administrative visibility. Still, its impact on service quality and trust remains limited by network stability, digital literacy gaps, and mandatory face-to-face verification. This research contributes to digital public administration by positioning local digital transformation as a socio-technical innovation management process, rather than simply a technology procurement project. Practical implications include the need for an integrated service architecture, continuous capacity building of civil servants, human-centered service design, and inclusive digital literacy support.